EFFECT OF SAGO CATERPILLAR (RHYNCOPHORUS BILINETAUS VAR PAPUANUS) OIL EXTRACT AGAINST LYMPHOCYTE, LEUKOCYTE, AND CD4 LEVELS OF HUMAN IMMUNODEFICIENCY VIRUS PATIENTS IN PAPUA, INDONESIA - TINGGINEHE, ROSMIN MARIATI; Makaba, Sarce (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Human immunodeficiency virus (HIV)/acquired immune deficiency syndrome has become a pandemic worrying the world community. The HIV virus destroys the human immune system causing the person can lose their immune system so that they are easily infected and die from complications of various diseases. The purpose of this study was to determine whether the administration of sago caterpillars oil extract can increase levels of lymphocytes, leukocyte, and CD4 on HIV patients in Papua. Methods: The research method utilized a true experiment with a randomized control group design. Data collection techniques included several double-blind stages. The first, selection of sago caterpillar and was done extraction process to get oil then packed into capsules. The second step, intervention in 14 subjects randomly which divided into 3 groups, the group receiving flour extract (n=5), oil extract (n=5), and the control group with placebo (n=4). During the intervention, all subjects were placed in a shelter and got the same food and the same activity. Results: Based on paired sample test statistical tests, it was found that there were significant differences before and after intervention in the group given oil preparations (p=0.023 <0.05) and control (p=0.043<0.05). Measurement of leukocyte levels showed that the group of oil and flour preparations had significant differences before and after intervention (p=0.040 <0.05, p=0.010), whereas in the control group, there were no significant differences between before and after administration (p=0.182>0.05). All intervention groups experienced an increase in CD4 cell count in the blood. The results of paired sample test statistical tests CD4 levels before and after the intervention showed a significant relationship in the three treatment groups (p=0.001; 0.025; 0.015 <0.05). Conclusion: The administration of sago caterpillar oil extract gives a significant effect against the rising of lymphocyte, leukocyte, and CD4 level in HIV sufferers blood.